Kewenangan Pemerintah Daerah Dalam Perjanjian Kerjasama Internasional - Wattimena, Jose Christy; Nendissa, Renny Heronia; Daties, Dyah Ridhul Airin (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The development of the international community which has an impact on political and economic regionalization also has demands for local autonomy affecting patterns of international relations, in line with this, new actors have emerged where local governments have played a role in entering into international cooperation agreements.Purposes of the Research: This writing aims to identify and analyze the position of local government as a legal subject in international cooperation agreements and to determine and analyze the form of local government authority in entering into international cooperation agreements.Methods of the Research: The research method used is normative juridical with a problem approach using a statutory approach and a conceptual approach. The legal materials used consist of primary and secondary legal materials with legal material collection techniques carried out through library research.Results of the Research: The results of this study conclude that the regional government in entering into international cooperation agreements cannot be seen as a proper subject of international law, in entering into international cooperation agreements the position of the regional government remains a representation of the state. The form of regional government authority in entering into international agreements is a combination of delegation and mandate because it is a pre-existing delegation of authority from the center to the regions and acts on behalf of the state, in this case the authority giver.